Longitudinal patterns of cocaine use among patients receiving injectable hydromorphone or diacetylmorphine for the treatment of opioid use disorder: A growth curve modeling approach. (1st January 2021) - Palis, Heather; Guh, Daphne; MacDonald, Scott; Harrison, Scott; Brissette, Suzanne; Marsh, David C.; Schechter, Martin T.; Oviedo-Joekes, Eugenia
Highlights: Injectable opioid agonist treatment engagement was related to reduced cocaine use. Women reported more cocaine use compared to men, at baseline and over 24-months. Cocaine use declines were greater for people with longer cocaine use histories. Abstract: Background and aims: Cocaine use is prevalent among people receiving injectable opioid agonist treatment. Investigations of cocaine use in this population have been descriptive and the potential heterogeneity existing in patterns of use have not been characterized. As such, among patients receiving injectable opioid agonist treatment, this study aimed to: 1) quantify intra- and inter-individual variation in cocaine use over 24-months and; 2) determine how predictors of interest explained this variation. Methods: Participants were patients receiving injectable opioid agonist treatment for opioid use disorder. Study visits were completed at baseline prior to receiving treatment, and 3, 6, 9, 12, 18, and 24 months after baseline. A multi-level regression approach to growth curve modeling was employed to estimate and explain intra- (within-person) and inter-individual (between-person) variation in cocaine use. Results: Significant intra and inter-individual variation in cocaine use was identified over 24-months. Treatment engagement was on average associated with reductions in the prior month number of days of cocaine use (range: 0–30)(Estimate (standard error): -0.05(0.02), p = 0.003). On average, men reported less cocaine use compared to women (Estimate (standard error): -5.91(1.57), p=<0.001), and participants reporting ever regularly using cocaine at baseline reported more cocaine use over 24-months compared to participants reporting never regularly using cocaine (Estimate (standard error): 4.72 (1.91), p = 0.013). Conclusions: Significant reductions in cocaine use were observed and significant heterogeneity in patterns of cocaine use was identified. These heterogeneous cocaine use profiles suggest that an individualized approach to care will be critical in responding to patients' cocaine use in injectable opioid agonist treatment.